Analisis faktor kesalahan sebagai unsur dolus dalam tindak pidana merampas nyawa milik orang lain dalam perkara no 328/PID/2017/PT.DKI - Koko Joseph Iritanto; Dian Andriawan Daeng Tawang (Jurnal Hukum Adigama, 2018)
Koko Joseph irianto, (205130115), Faculty of Law at Tarumanagara University, with the title of the thesis "Analysis of the error factor as an element of dolus in a crime to take the life of another person in a case NO: 328 / PID / 2017 / PT.DKI ". Under the guidance of Mr. DR.DIAN ADRIAWAN, S.H, M.H. This study aims to analyze the legal arrangements regarding criminal acts of premeditated murder by a group of people in Decision Number: no: 328 / PID / 2017 / PT.DKI. This research was carried out in the city of Jakarta by selecting agencies related to this case namely in the Jakarta High Court. Data collection method used is documentation study method then the data obtained is analyzed descriptively qualitative so as to reveal the expected results and conclusions on the problem. The results of this study indicate that 1) Legal arrangements for criminal acts of murder have been regulated in general in the Criminal Code (KUHP). And the murder plans to be in article 340 of the Criminal Code 2) The application of the material criminal law to the perpetrator of the Murder criminal act is appropriate, as regulated and threatened with criminality in Article 340 of the Criminal Code. Judicial legal considerations in imposing death penalty on 2 and 1 prisoners for life of the defendants from 4 perpetrators who are still alive is correct. The conviction of the defendant was considered to have fulfilled a sense of justice for all parties.